A panel of five microsatellites as an alternative to mitogenome sequencing for investigating the genetic diversity of Echinococcus granulosus sensu stricto from global to farm scale - Umhang, Gerald; Bastid, Vanessa; Rinaldi, Laura; Pepe, Paola; Ciccone, Elena; Sotiraki, Smaragda; Aguayo, Jaime (Elsevier, 2026)
While the molecular identification of Echinococcus granulosus species is essential for surveillance, a detailed investigation of the parasite's genetic diversity would offer a more accurate understanding of its transmission. This may be done by partial or whole mitochondrial genome sequencing, but both cost and time requirements limit routine application. Microsatellites are an alternative approach as they are a rapid, simple, highly discriminative, and low-cost tool. Our research project was designed to obtain a panel of microsatellite targets for population genetic analyses to describe the genetic diversity of E. granulosus sensu stricto (s.s.) at the global to farm scale. A panel of five informative microsatellite loci for population genetic analysis of E. granulosus s.s. was developed and validated. A total of 145 isolates from 11 countries were used to evaluate the panel at the international level. Additionally, 131 samples from sheep and cattle across six regions in southern Italy were analyzed to assess the panel's usefulness at both the regional and farm scale. Population genetics showed high genotypic diversity. Simpson's index gave high values (0.94-0.98) for the expected heterozygosity (0.80 to 0.87). Discriminant analysis of principal components (DAPC) revealed the structure of populations for each country, with Greece distinctly distant from Algeria, Italy, and Tunisia. This was also confirmed by FST values. DAPC further revealed a genetic structure among the farms from the Italian regional sample set, with three different clusters explained by different farming practices. This microsatellite panel can provide data relevant for E. granulosus s.s. population genetics from global to farm scale, making it a low-cost, simple alternative to full mitochondrial genome sequencing for analyzing numerous samples and obtaining a detailed overview of genetic diversity, an input that is useful for cystic echinococcosis control programs.
Keywords: Echinococcus granulosus sensu stricto; Microsatellite target; Population genetics; Infection event